Ethical focus on management results - Marleide Cerqueira de Oliveira; Vagner Antonio Marques; Jacqueline Veneroso Alves da Cunha; Poueri do Carmo Mário (Revista Contemporânea de Contabilidade, 2012)
http://dx.doi.org/10.5007/2175-8069.2012v9n18p119